Peningkatan Earning Before Interest and Tax (EBIT) melalui Penerapan Green Accounting - Rachma Agustina; Dwi Ari Pertiwi; Deasy Ervina; Meta Ardiana (Majalah Ekonomi, 2022)
This study aims to analyze the increase in eco efficiency with the application of green accounting. Data collection techniques using literature study, observation, interviews and documentation. Checking the validity of the data through extension of participation, persistence of observation, and triangulation of data. The results showed that Lumintu farm’s had implemented green accounting through the stages of identifying costs for handling the impact of negative externalities on production, the recognition stage, the measurement stage, the presentation stage through the income statement and the stage of disclosing the costs or costs incurred by the company for environmental management. The good environmental performance of the entity also has an impact on the positive response of consumers so that it can increase profits or EBIT..